2019
DOI: 10.3389/fmicb.2019.02400
|View full text |Cite
|
Sign up to set email alerts
|

The Myosin Motor Domain-Containing Chitin Synthases Are Involved in Cell Wall Integrity and Sensitivity to Antifungal Proteins in Penicillium digitatum

Abstract: Penicillium digitatum is the main postharvest pathogen of citrus fruit and is responsible for important economic losses in spite of the massive use of fungicides. The fungal cell wall (CW) and its specific component chitin are potential targets for the development of new antifungal molecules. Among these are the antifungal peptides and proteins that specifically interact with fungal CW. Chitin is synthesized by a complex family of chitin synthases (Chs), classified into up to eight classes within three divisio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 88 publications
(188 reference statements)
2
5
0
Order By: Relevance
“…In this study, the fewer and weaker blue fluorescence septa were observed under C 12 O 3 TR stress (Figure 5), indicating that the chitin content in the cell wall was influenced by C 12 O 3 TR treatment. This result was similar with the effect of antifungal proteins on cell wall chitin (Gandía et al, 2019). It was reported that the changes of chitin content was related to the activity of related enzymes, such as β-1, 3-glucan synthase and chitinase (OuYang et al, 2019).…”
Section: Discussionsupporting
confidence: 85%
“…In this study, the fewer and weaker blue fluorescence septa were observed under C 12 O 3 TR stress (Figure 5), indicating that the chitin content in the cell wall was influenced by C 12 O 3 TR treatment. This result was similar with the effect of antifungal proteins on cell wall chitin (Gandía et al, 2019). It was reported that the changes of chitin content was related to the activity of related enzymes, such as β-1, 3-glucan synthase and chitinase (OuYang et al, 2019).…”
Section: Discussionsupporting
confidence: 85%
“…These effects have already been described in other cases where the cell wall was clearly damaged, for instance, in PdCrz1 mutants [26]. This result was also similar to the one observed with the addition of antifungal proteins on cell wall chitin [34]. The cell membrane plays a relevant role in maintaining cell viability because it represents a barrier by separating the cell from its environment, and is also a means of exchange of substances and energy between the cell and the surrounding environment.…”
Section: Discussionsupporting
confidence: 83%
“…The cell wall is the first barrier of filamentous fungi resist environmental pressures and is crucial for maintaining the normal growth of fungal ( Gandía et al, 2019 ). In the current study, chitin synthase (gi| 859266290 ), endoglucanase (gi| 859262625 ), 1,3-β-glucanosyltransferase (gi| 859262943 ), and β-glucosidase (gi| 859260053 ), which are important cell wall-related proteins, were overexpressed.…”
Section: Discussionmentioning
confidence: 99%